Maya (smart mirror) - Tanggamani, Vani; Minhad, Siti Fatimah Noor; Suhaimi, Nur Syazwani; Isderis, Dania Arisya; Mohd Jaffar, Nor Hafizatul Madihah; Haizam, Nurhuda Hanisah; Megat Mahayudin, Puteri Fadlin Sakina (Universiti Teknologi MARA, Kedah, 2023)
The history of mirrors starts from Justus von Liebig, who invented modern mirrors in Germany in 1835. Yet, mirrors had actually been used in Turkey approximately 8000 years ago, used in Iraq and Egyptwhere the mirrors were made of copper. Nowadays, mirrors have been part of human needs. People use mirrors daily for their appearance especially when there is an event that requires them to go out of theirhouse. This could help a certain group of people to find a solution in their daily routine. They show us what we look like, they let us examine ourselves, and they can give us a glimpse of our ancestry and heritage. Sometimes a mirror will show us a part of ourselves that we did not notice before, and there is beauty in that. Maya is the best to find the best ingredients that are suitable for their skin type and skin concern. By this, people will be interested to invest in the smart mirror since the function of it will literally help them to solve some of their problems. Smart mirror’s users will not have to worry anymore about their hesitation with their skin, hair and cosmetics problems after using our smart mirror. Six types of functions provided with the smart mirror will give the best experience for the users that reallyhelp them to cope with their life.